2017
DOI: 10.1111/imm.12799
|View full text |Cite
|
Sign up to set email alerts
|

Age has a role in driving host immunopathological response to alphavirus infection

Abstract: SummaryAlphaviruses are a group of arthropod-borne pathogens capable of causing a wide spectrum of clinical symptoms, ranging from milder symptoms like rashes, fever and polyarthralgia, to life-threatening encephalitis. This genus of viruses is prevalent globally, and can infect patients across a wide age range. Interestingly, disease severity of virus-infected patients is wideranging. Definitions of the pathogenesis of alphaviruses, as well as the host factors influencing disease severity, remain limited. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 155 publications
1
12
0
Order By: Relevance
“…2d) was decreased in the acute phase when compared with the control group. 21 In summary, our data demonstrate for the first time the role, and putative mechanisms, of CD8 + T lymphocytes from CHIKV-infected patients in the acute and chronic phases of infection. 16 However, the viral persistence was not associated with inflammatory cytokines, such as interferon-c, tumour necrosis factor-a and IL-1b.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…2d) was decreased in the acute phase when compared with the control group. 21 In summary, our data demonstrate for the first time the role, and putative mechanisms, of CD8 + T lymphocytes from CHIKV-infected patients in the acute and chronic phases of infection. 16 However, the viral persistence was not associated with inflammatory cytokines, such as interferon-c, tumour necrosis factor-a and IL-1b.…”
Section: Discussionmentioning
confidence: 56%
“…A recent review showed important points related to several age-dependent differences that could influence disease severity and host recovery in alphavirus infection. 21 In summary, our data demonstrate for the first time the role, and putative mechanisms, of CD8 + T lymphocytes from CHIKV-infected patients in the acute and chronic phases of infection. Expression of markers demonstrated that the cytolytic exocytosis mechanism is activated in this pathology, indicating the ability of these cells to eliminate CHIKV.…”
Section: Cd8 + T Cells Play Important Roles Against Viral Infection mentioning
confidence: 56%
“…Host-mediated immunopathology is sometimes increased in the elderly during immune challenges 5 , further highlighting the importance of studying adaptive immunity in the context of ageing. A number of phenotypic and functional alterations have been linked to dysfunctional adaptive immunity, including the diminished production of new naïve B and T cells [6][7][8] , increased host-immunopathology during viral infections and disease 5,9 , increased exhaustion and elevated expression levels of dysfunction markers 10,11 . A prominent example revealed that CD8 T cells up-regulated classical exhaustion markers (PD-1, LAG3, 2B4, CD160) when comparing 4-month-old to 12-month-old mice.…”
Section: Introductionmentioning
confidence: 99%
“…In West Nile Virus infection, on the other hand, a protective role of NKC has been invoked and enhanced susceptibility comes with ageing . Chan and Ng point out that a key factor generally in evaluation of innate and adaptive immune subsets to arboviral disease outcome is the differential impact of host immune senescence …”
mentioning
confidence: 99%
“…10 Chan and Ng point out that a key factor generally in evaluation of innate and adaptive immune subsets to arboviral disease outcome is the differential impact of host immune senescence. 11 Analysis of changes to the Treg compartment can be an important step in evaluating the balance between host defence and regulation of collateral damage in achieving a balance between pathogen clearance and immunopathology. All of the Flaviviruses that infect man are associated with severe immunopathological manifestations, making regulation an important question.…”
mentioning
confidence: 99%